Regional scenarios to guide policies, investments and institutional change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Scenarios are plausible stories about the different ways in which economic development might occur in the future and the role that agriculture may play, developed collectively based on information from participants with different, and sometimes opposing, experiences and views. CCAFS has promoted the scenario approach as a way of bringing these views and interests together to create credible stories of what might happen and what might be done about it. CCAFS regional scenarios are developed from diverse stakeholder knowledge and quantified through agricultural economic and land-use models. To date, over two hundred and forty organizations, representing government departments, regional economic bodies, CSOs and NGOs, farmer organizations, private sector investors, academia and the media have participated in scenario processes in the five CCAFS regions. CCAFS’s forward-looking and evidence based scenarios are used by decision-makers to guide policy and investment choices along impact pathways at regional, national and sub-national levels.